Pengaruh Kegunaan, Informasi, Layanan Interaksi, User Interface Dan User Experience Terhadap Kepuasan Pengguna Website Detik.Com Metode Webqual 4.0, User Experience Questionnaire (Ueq) Dan Eight Golden Rules - Muhamad Amirlulah Syaputra (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
Detik.com is one of the news portal websites that had the second most visits in Indonesia in the early days of the Covid-19 pandemic. The website Detik.com supports mobile and desktop display making it easier for users to access detik.com without fear of experiencing gadget or device limitations. While there is minimal information about Covid-19 websites Detik.com it is expected that visitor traffic increases but website statistics Detik.com according to www.similarweb.com decrease after March 2020, then the assessment of website performance Detik.com is very necessary. This assessment is to find out if the website Detik.com has provided satisfaction to users. Detik.com has given satisfaction to the user. Based on this research that should be focused on improving the quality of information, the quality of user interface and the quality of user experience. So the authors conducted research efforts using the Webqual method, User Experience Questionnaire (UEQ) and Eight Golden Rules as well as quantitative-descriptive approaches. The results include usability quality, information quality, quality of service interaction, quality of user interface and quality of user experince has a positive influence on the level of user satisfaction.